Overcoming Asia's currency and financial crises a theoretical investigation - Kunimune Kozo (Chiba Institute of Developing Economies, 2004)
This volume brings together a number of research project papers which examines the high interest rate policy intended to stave off a currency crisis & corporate restructuring policies for revitalizing economic activity after the Asian currency crisis.
Keywords: Asia; Macroeconomic policies